THE STRATEGIES OF NTB MARITIME AND FISHERIES AGENCY IN BUILDING MEDIA RELATION WITH JOURNALIST TO DEVELOP POLICY PRGRAM PUBLICITY: STRATEGI DINAS KELAUTAN DAN PERIKANAN NTB DALAM MEMBANGUN HUBUNGAN MEDIA DENGAN JURNALIS DALAM MENGEMBANGKAN PUBLISITAS PROGRAM KEBIJAKAN - Cory Tri Sabrina; Eka Putri Paramita; Novita Maulida (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2024)
Considering the development of the digital era, all information and news can easily accessible anywhere. However, it is not impossible that the information disseminated is not only good news, but also a lot of fake news spreads very rapidly. The role of Public Relation in these cases in disseminating news is by collaborating with the media. Publicity that applied by Public Relation to build positive image if institution through media relation is applied in various sectors, one of them is the maritime and fisheries sector. The NTB Maritime and Fisheries Office, which shade the maritime and fisheries sector in NTB, has been conducting media relation with the press for more than ten years. In the implementation of media relations, there are strategies carried out including by serving the media, by supplying good copy, by building personal relationship with the media, by establishing a reputation for reliability, by cooperation in providing the material, and by verification facilities. Then the NTB Maritime and Fisheries Office has media relation activities with the journalist include press conference, reception press, radio talk shows and electronic talk shows, media events, and press release.